MTUN: The history and future of public technical universities in Malaysia - Miskon, Muhammad Fahmi (Malaysia Board of Technologists (MBOT), 2016)
In April 1999, Malaysia proposed the establishment of technical-based institutes of higher learning, with a focus on 70% hands-on learning and 30% theory. The cabinet committee report in 1979 proposed a school system with academic and technical/vocational streams. By the 7th Malaysia Plan, there were 90 technical schools with 36,000 students. Technical school-leavers could not enroll for a Bachelor degree due to the theoretical approach in most public institutes of higher learning. Diploma graduates came from polytechnics, British Malaysian Institute, German Malaysian Institute, Malaysia France Institute, and government public skill centres. The establishment of technical universities was a proactive move to increase the number of skilled engineers.